Transfer of strength and power training to sports performance - Young, W. B. (International Journal of Sports Physiology and Performance, 2006)
The purposes of this review are to identify the factors that contribute to the transference of strength and power training to sports performance and to provide resistance-training guidelines. Using sprinting performance as an example, exercises involving bilateral contractions of the leg muscles resulting in vertical movement, such as squats and jump squats, have minimal transfer to performance. However, plyometric training, including unilateral exercises and horizontal movement of the whole body, elicits signifi cant increases in sprint acceleration performance, thus highlighting the importance of movement pattern and contraction velocity specifi city. Relatively large gains in power output in nonspecific movements (intramuscular coordination) can be accompanied by small changes in sprint performance. Research on neural adaptations to resistance training indicates that intermuscular coordination is an important component in achieving transfer to sports skills. Although the specifi city of resistance training is important, general strength training is potentially useful for the purposes of increasing body mass, decreasing the risk of soft-tissue injuries, and developing core stability. Hypertrophy and general power exercises can enhance sports performance, but optimal transfer from training also requires a specifi c exercise program.